2012
DOI: 10.1037/a0024454
|View full text |Cite|
|
Sign up to set email alerts
|

Beyond cumulative risk: Distinguishing harshness and unpredictability as determinants of parenting and early life history strategy.

Abstract: Drawing on life history theory, Ellis and associates' (2009) recent across- and within-species analysis of ecological effects on reproductive development highlighted two fundamental dimensions of environmental variation and influence: harshness and unpredictability. To evaluate the unique contributions of these factors, the authors of present article examined data from a national sample 1364 mothers and their children participating in the NICHD Study of Early Child Care and Youth Development. Harshness was ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
586
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 493 publications
(635 citation statements)
references
References 74 publications
43
586
2
4
Order By: Relevance
“…A longitudinal study (Simpson, Griskevicius, I-Chun Kuo & Sung, in press) found that sexual and criminal behaviour at age twenty-three was predicted by the level of unpredictability experienced by 11 age five (indexed by changes to mothers residence, employment and partners). Belsky et al (2011) demonstrated similar results; focusing on sexual behaviour at age fifteen as the dependent measure.…”
supporting
confidence: 53%
“…A longitudinal study (Simpson, Griskevicius, I-Chun Kuo & Sung, in press) found that sexual and criminal behaviour at age twenty-three was predicted by the level of unpredictability experienced by 11 age five (indexed by changes to mothers residence, employment and partners). Belsky et al (2011) demonstrated similar results; focusing on sexual behaviour at age fifteen as the dependent measure.…”
supporting
confidence: 53%
“…If testicular volume is causal, individual differences in testes may be governed by evolved genetic influences, or they may be shaped by environmental factors analogous to the role of father absence in the timing of female menarche (36). Similar effects of early life experience on reproductive strategies have been found for males, with stress and unpredictability correlated with relatively earlier and more promiscuous sexual activity (37). It is possible, for example, that fathers in the present study who invest more in reproductive biology and less in parenting had experienced a more stressful and unpredictable childhood, or one without a father present.…”
Section: Discussionmentioning
confidence: 65%
“…-287-moderated by lower SES or inconsistent resources (e.g., Belsky et al, 2012;Deardorff et al, 2011;Ellis et al, 2009;James-Todd, Tehranifar, Rich-Edwards, Titievsky, and Terry, 2010;Simpson, Griskevicius, Kuo, Sung, and Collins, 2012). New experimental studies have even found that simply reminding women about paternal absence or disengagement (via priming) can alter their behavior (sexual thought/permissiveness, condom use) in ways consistent with psychosocial acceleration theory (DelPriore and Hill, 2013).…”
Section: Father Absence and Menarchementioning
confidence: 82%